Severe Limb Weakness, Bradycardia, and AV Block in Periodic Paralysis Hypokalemia - Irfan Nugraha, Dyandika (Acta Neurologica Indonesia, 2024)
Introduction : The Periodic Paralysis is an uncommon group of disorders that can cause of sudden extremity weakness. The Hypokalaemia also may present with cardiovascular and neuromuscular abnormalities. Hypokalaemia can lead to clinically significant life-threatening cardiac rhythm abnormality. We present a case of a 32-year-old Javanese with sudden onset paralysis of his extremities. Laboratory evaluation revealed a significant low potassium level. The ECG showed significant bradycardia and AV block. The patient weakness improved gradually after repletion of the low potassium. The ECG also improved to normal sinus rhythm. The patient was discharged without any neurologic deficits. Case Report : A 32 year-old Javanese male presented to the emergency room with sudden four extremity weakness. The patient complain begin when awoke at early morning, and unable to move his upper or lower extremities. The weakness was bilateral and predominantly involved both the proximal muscles of the shoulders and hips as well as the distal extremities. Discussion : We report a case of sudden onset bilateral limbs flaccid weakness. The final diagnosis was periodic paralysis hypokalaemia. Treatment of periodic paralysis hypokalaemia consists of slow and careful correction of low potassium level. The very rapid correction exposes the risk of hyperkalaemia. Close monitoring by neurological examination and repeat examination potassium level is essential. Conclusion : We report a case of sudden onset paralysis and significant cardiac abnormality related with very low potassium level. The paralysis and ECG abnormality resolved completely following potassium replacement. Keywords: Hypokalemia, Periodic Paralysis, AV block, weakness